KEBERADAAN TELUR CACING PARASIT PADA SISWA SD DI SEKITAR INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) TERPADU KOTA MALANG DAN HUBUNGANNYA DENGAN KEPADATAN TELUR CACING PADA AIR LIMBAH PERUMAHAN DI IPAL TERPADU - Sofia Ery Rahayu (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2006)
The research to find out the existence, kinds, and prevalence of parasitic worm egg on the hands and nails of elementary school students lives in IPAL area also its existence in the water of housing dump has been conducted recently. It also analyze the correlation between the number of parasitic worm egg population on the elementary school students hands and nails lives in IPAL area and the water of housing dump in IPAL Terpadu Kota Malang. The research used descriptive explorative method and conducted on June–August 2004. The sample of parasitic worm egg is taken from elementary school students hands and nails ilves in IPAL area and the water of housing dump in IPAL Terpadu Kota Malang. The elementary shools taken as samples area SDN Tlogomas 1, SDN Bareng 3, SDN Mulyorejo 1, SDN Mergosono 1, and SDN Mergosono 2. The locations of IPAL Terpadu Kota Malang used in this research are Tlogomas, Bareng, Mulyorejo, Mergosono Gang 1, and Mergosono Gang 3 area. Identification of worm egg is conducted in Biology Departement, Faculty of Mathematics and Science, State University of Malang. The data taken are in the form of kinds of parasitic worm egg based on morphology characteristics and it will be analyzed descriptively. Then the prevalence of each kind of parasitic worm egg will bw counted. Then the researchers do some correlation analysis. Findings of this research show that from 5 samples of elementary school used in this research only the hands and nails of students in SDN Mulyorejo 1 have no human parasitic worm egg while in four others found 4 kinds of human parasitic Nematoda they are Ascaris lumbricoides, Enterobius vermicularis, Trichuris trichiura, and Ancylostoma duodenale. From 5 areas of IPAL Terpadu Kota Malang used in this research only in Bareng area it is not found while in four others found 3 kinds of worm egg they are A. lumbricoides, E. vermicularis, and T. trichiura. Egg prevalence of each kind of parasitic worm species on the elementary shool students lives in IPAL Kota Malang area are A. lumbricoides is 65.22%, E. vermicularis is 21.47%, T. trichiura is 11.59%, and A. duodenale is 1.45%. Egg prevalence os each parasitic worm species in IPAL Terpadu Kota Malang are A. lumbricoides is 88.40%, E.vermicularis is 10.15%, T. trichiura is 1.45%, and A. duodenale is 0%. In general is a relationship between the number of parasitic worm egg on the hans and nails of elementary school students lives in IPAL area and worm egg in the water of housing dump in IPAL Terpadu Kota Malang.